First aid for the psychiatry clerkship - Blitzstein, Sean M.; Ganti, Latha; Kaufman, Matthew (McGraw Hill, 2022)
"Each of the chapters in this book contains the major topics central to the practice of psychiatry and has been specifically designed for the medical student learning level, to excel in the clerkship (shelf exams), as well as the USMLE Step 2 and 3 exams"--